Comprehensive Cloud Solution for Secure Text Transmission: Enhancing Privacy and Integrity in Digital Communication - Elangovan G, Elangovan G; Leela Krishna, Sanaboina; Dhanalakshmi R, Dhanalakshmi R; Mary. J, Prisca; Ramasamy Reddy, Viswanathan; Vengatesh, T. (Journal of Neonatal Surgery, 2025)
Given the increasing risks to data integrity and privacy in the current digital world, it is imperative that text data be transmitted securely over cloud platforms. Although cloud computing provides a scalable and economical infrastructure, it also puts private data at risk from cyberattacks, illegal access, and data breaches. Through the use of cutting-edge encryption algorithms, secure authentication mechanisms, and data integrity verification methods, this article offers a comprehensive cloud solution intended to improve the privacy and integrity of digital communication. By using a multi-layered security strategy and end-to-end encryption, the solution reduces the possibility of illegal parties intercepting data whether it is in transit or at rest. A hybrid encryption paradigm is used to increase security, combining symmetric encryption for effective data protection with asymmetric encryption for key exchange. This guarantees that potential attackers cannot understand the data, even if it is intercepted. Furthermore, data integrity is preserved by the use of secure hashing methods, which enable recipients to confirm the accuracy and completeness of the information they have received. Role-based access control (RBAC) and multi-factor authentication (MFA), which limit access to authorized users and provide accountability, are complementary to this architecture. Because the suggested solution is cloud-agnostic, it may be deployed easily across different cloud providers while upholding uniform security standards. Performance tests show that there is little impact on latency, indicating that the method is viable for real-time applications. Additionally, the system is made to adhere to legal requirements like GDPR and HIPAA, which addresses privacy issues and boosts user confidence. This all-inclusive method of secure text transmission is appropriate for sectors with strict security requirements, such as government, healthcare, and finance, since it not only protects data but also strengthens the dependability and integrity of digital communications in a cloud environment.